The genus Clerotalia Jacoby of Taiwan (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng (Zootaxa, 2018)
Six new species within the genus Clerotalia Jacoby are described from Taiwan based on study of more than 340 specimens: C. cheni sp. nov., C. jungchani sp. nov., C. meihuai sp. nov., C. tsoui sp. nov., C. wulaiensis sp. nov., and C. yuae sp. nov.. Clerotilia shirozui (Kimoto, 1969) is regarded as a junior synonym of C. formosana (Chûjô, 1963). Adults were collected by sweeping food plants, including Rhamnus nakaharae and R. formosana (Rhamnaceae).